Laboratory findings of patients with severe dengue in a Puerto Maldonado hospital, Peru - Rojas Jaimes, Jesús (2014)
Background: Puerto Maldonado is the capital of Madre de Dios Department and is a dengue endemic zone. Severe (hemorrhagic) dengue includes shock, respiratory distress and involvement of target organs. Objectives: To identify laboratory findings in severe dengue patients. Design: Retrospective cross-sectional study. Setting: Central Laboratory and Epidemiology Department, Santa Rosa Hospital, Puerto Maldonado, Madre de Dios, Peru. Materials: Fifty-five medical records of patients with severe dengue hospitalized in the intermediate care unit from June 2010 through November 2011. Methods: Results of laboratory tests taken during hospitalization were analyzed. Main outcome measures: Transaminases, creatinine, complete blood count and urinalysis. Results: Most patients came from Puerto Maldonado (84%). The 40-49 years-old group was the most affected (32%). Out of 55 patients, 83% showed increased serum transaminases and creatinine. Platelet count was within normal limits, except in the 10-19 year-old group (11%), which showed serum platelets levels less than 150 000/mL. Conclusions: Most patients hospitalized for severe dengue at Puerto Maldonado presented increase in serum transaminases and creatinine. Platelet count was within normal limits but low in the 10-19 year-old group.